Effect of parity, stage of lactation and udder type on milkability of crossbred dairy cows milked in automated Herringbone milking parlour - FAHIM, A; KAMBOJ, M L; PRASAD, S; SIROHI, A S; BHAKAT, M; MOHANTY, T K; MALHOTRA, R (The Indian Journal of Animal Sciences, 2017)
The aim of the study was to investigate the effect of parity, stage of lactation and udder type on milkability of crossbred dairy cows milked in automated Herringbone milking system. Crossbred cows (218; Karan Fries and Karan Swiss) of different parities, stages of lactation and udder types were milked in 8×2 low-line automated Herringbone milking parlour having automatic cluster removal (ACR) settings for a period of 3 months. The milkablity of cows in automated herringbone milking parlour was based on parameters such as total milk yield, milk yield/session, machineon time, yield first 2 min, and milk flow rates generated automatically in herd management Software during each session of milking. The results showed that milkability of cows was affected significantly based on parity and stage of lactation. The udder types had no effect on milkability except type D (pendulous) udders having least flow rate, which caused increased machine-on time. The overall mean milk flow rates over different intervals during the first two minutes of milking differed significantly in parity and udder types. Similarly, significant differences were observed in the flow rates over different intervals of milking.The milking efficiency benchmarks in terms of cow throughput and milk harvesting efficiency with 2 operators in the milking pit were 69.75±0.57 cows/ h and 305.21±2.75 kg/h, respectively. The operators had idle time during milking in batches of around 4.28 minutes/batch. It can be concluded from the present study that the milkability of crossbred dairy cows was significantly affected by parity, stage of lactation and type of udder in automated Herringbone milking parlour.